Dialektika dan Proses Inkulturasi Agama dan Budaya Lokal di Indonesia - Supriadin, Irwan; Pababari, Musafir (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This research examines the relationship between religion and culture in Indonesian society, focusing on the processes of dialectics and inculturation that enrich both elements and shape social identity. Using a qualitative approach and literature review, the study traces how religion, particularly Islam, integrates with local culture in various traditions such as Ngurisang in Sasak and Rebo Wekasan in Banjarnegara. The analysis, based on Clifford Geertz’s cultural theory, Pierre Bourdieu’s Habitus, and Emile Durkheim’s social solidarity, demonstrates that religion is not only a doctrine but also an ethical foundation and a symbol of culture that strengthens social bonds and collective identity. The research findings reveal that the inculturation of religion into local culture creates social harmony, contributes to religious moderation, and prevents identity conflicts. The study recommends an inclusive approach and cross-cultural dialogue to strengthen social cohesion in Indonesia’s pluralistic society.